Descrição da configuração da linha de costa ao longo do Arco Litoral Tróia-Sines. - Gama, Cristina (2009)
Aerial photography of 1996, 2001 and 2002 were used to obtain the alongshore characterization of subaerial beach width of the Tróia-Sines embayed coast. The Digital Shoreline Analysis System (DSAS) extension for ArcGIS v.9.0 was used to describe the variation of the shoreline configuration. The Tróia-Sines embayed coast is characterized by the southward increase of the beach width and berm high. Despite the similarity between the alongshore shoreline configuration, the variation of the subaerial beach width, allowed the definition of four main sectors. A singular accretion tendency is observed at the northern extreme of the Tróia spit. An erosion spot is located close to the Sol-Tróia resort.